Finite Element Analysis of Effect of Double Shot Peening on Residual Stresses of 18CrNiMo7-6 Gear Steel - Wang Zhen; Sun Hao; Wang Guohao (Jixie chuandong)
Addressing the issue of unequal distribution of residual compressive stress and high surface roughness that occurs on gears after shot peening treatment, this research examined the impact of double shot peening technology on the surface integrity of 18CrNiMo7-6 carburized gear steel. Using the Abaqus software,a random pellet distribution shot peening model was created. The effects of shot peening parameters such as shot peening speed and shot diameter on the surface residual stress and surface topography of 18CrNiMo7-6 carburized gear steel were analyzed. The findings indicate that double shot peening yields more uniform surface plastic deformation in comparison to single shot peening. Additionally, the second shot peening can significantly increase the residual compressive stress on the surface of the material, and shifts the depth of maximum residual compressive stress value towards the surface. However, this process does not significantly affect the depth of the residual compressive stress layer. Through variance analysis, when the shot peening coverage is 100%, the second shot peening strengthening is carried out by using the processing parameters with smaller shot peening intensity,which has a better improvement effect on the uniformity of surface layer residual compressive stress, and the uniformity of surface residual compressive stress is increased by 28.76%.